2018
DOI: 10.37706/ijaz.v3i2.80
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Zakat, Infak, and Sadaqah Distribution on Poverty Alleviation Based on the CIBEST Model (Case Study: Jogokariyan Baitul Maal Mosque, Yogyakarta)

Abstract: The Special Region of Yogyakarta is one of the provinces with a high incidenceof poverty onJava Island. The number of mosques and the increase of zakat funds, infak, and sadaqaheach year is not sufficientto reduce the number of those in poverty. If the mosque is able tomanage the zakat, infak, and sadaqahfunds well, it can be predicted that the mosque would reduce poverty and increase the welfare of the community. This study aims to analyze the impact of zakat, infak, and sadaqah distribution in reducing pover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
5
0
3
Order By: Relevance
“…In the case of Yogyakarta, Indonesia, El Ayyubi and Saputri (2018) and Mulyani (2018) indicated an increase in welfare and a decrease in material poverty, spiritual poverty, and absolute poverty based on changes in the Islamic CIBEST’s poverty indexes for mustahiq households. These findings are also similar to those of Istikoma (2017), who studied fishermen households in Indramayu Regency, Ayuniyyah et al (2018) and Ayuniyyah (2019), who studied 1,309 households in West Java, Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of Yogyakarta, Indonesia, El Ayyubi and Saputri (2018) and Mulyani (2018) indicated an increase in welfare and a decrease in material poverty, spiritual poverty, and absolute poverty based on changes in the Islamic CIBEST’s poverty indexes for mustahiq households. These findings are also similar to those of Istikoma (2017), who studied fishermen households in Indramayu Regency, Ayuniyyah et al (2018) and Ayuniyyah (2019), who studied 1,309 households in West Java, Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several assumptions, techniques and orientations are observed in assessing efficiency. The most frequent used methodologies in assessing efficiency are the production and intermediate approaches (Ayyubi and Saputri, 2018) This production strategy is related to production theory, which addresses how producers or businesses create optimal output at the lowest possible production cost (Ryandono et al , 2021). The production approach is used in the analysis of Zakat Institutions to determine how much money can be collected and disbursed (Wahab and Rahman, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Jogokariyan Mosque located in Yogyakarta utilized the Baitul Maal as a means for economic empowerment, as reported by Ayyubi and Saputri in 2018. Multiple research studies conducted in Malaysia have demonstrated the utilization of cash waqf as a means to mitigate poverty through mosques (Ayyubi & Saputri, 2018) and to facilitate the growth of micro-small businesses (Imtiyaz & Razak, 2021). The study's presentation suggests that the utilization of Islamic social funds can be made more productive through mosque-based economic empowerment.…”
Section: Literature Reviewmentioning
confidence: 99%